Simulation-based performance comparison of two routing protocols for aircraft ad-hoc networks. (2016) - Khan, Saifullah; Kim, Ki-Il
Recently, new emerging research challenge, aircraft ad-hoc networks, has attracted considerable attention from the research community. Due to unique properties of aircraft ad-hoc networks, new routing protocols including geographical routing protocol for heterogeneous aircraft ad-hoc networks (GRHAA) and aeronautical routing protocol (AeroRP) have been proposed and analysed through simulation. However, since these protocols were compared with typical routing protocols for ad-hoc networks with simulation scenarios that were configured with unrealistic parameters for aircraft ad-hoc networks (AANETs), more reliable and credible simulation studies are essentially needed. Based on this demand, in this paper, we conduct simulation-based performance evaluation for two mentioned protocols with new relevant parameters. Based on simulation results, we can identify that two routing protocols are suitable for AANETs. Furthermore, GRHAA shows better performance than AeroRP in the aspects of packet delivery ratio and similar delay by the help of hierarchical architecture as well as more accurate position prediction scheme in heterogeneous environments.